Plasma prothrombin time and activated partial thromboplastin time as predictors of bleeding manifestations during dengue hemorrhagic fever - I. N. Budastra; B. N. P. Arhana; IB. Mudita (Indonesian Pediatric Society Publishing House, 2009)
Background  Massive bleeding and shock are complications  of dengue  hemorrhagic  fever (DHF)  that  are associated with high mortality. Impaired hemostasis, especially coagulopathy, contributes  to  bleeding manifestations in DHF. Parameters such as  activated partial thromboplastin time (APTT)  and  plasma prothrombin  time (PPT) indicate  the  impact  of  coagulation system. Objective  To  determine the relationship between  APTT  and PPT levels with bleeding manifestations in  DHF  patients. Methods  A prospective  cohort  study was applied to subjects diagnosed with  DHF  at  the  Infection  and  Tropical Diseases Division, Department  of  Child Health, Medical School, Udayana University, Sanglah Hospital, Denpasar, Indonesia. Laboratory tests  to  determine  APTT  and  PPT  were carried  out  on  the third, fourth,  and  fifth day after  the  onset  of  fever. Bleeding manifestations were examined in patients during their hospital stay. Univariate  and  Cox regression analyses were performed to examine relationship between  APTT  and  PPT  values with bleeding manifestations in  DHF  patients. Results  Forty-three children were enrolled in this study.  There was a significant relationship between increases in  APTT  value with bleeding manifestations in  DHF  patients [RR 2.79 (95%CI 1.68 to 4.69), P <0.01]. Cox regression analysis showed  that  only increased  APTT  values correlated with bleeding manifestations [RR 2.05 (95%CI 1.92 to 3.90), P  =  0.02]. Conclusion  APTT  values may be used  as  a predictor for bleeding manifestations  in  DHF.